Chromophobe Renal Cell Carcinoma With High-Grade Features: Can We Disregard the Grade?. Issue 6 (November 2017) - Banach, Bridget S.; Paner, Gladell P.
Abstract : Abstract: Chromophobe renal cell carcinoma (ChRCC) generally has a favorable behavior; however, a small subset of these tumors behaves aggressively. Grading of ChRCC has been challenging. Studies have shown that the traditional Fuhrman nuclear grade (FNG), or any of its components, is not useful as a prognostic indicator for ChRCC. Recently, the International Society of Urological Pathology (ISUP) recommended a novel grading (ISUP grade) for renal cell carcinoma (RCC) that relies mainly on nucleolar prominence, a component of FNG, and is applicable at least for clear cell RCC and papillary RCC. The ISUP also recommended that ChRCC should not be graded. Several other grading schemes have been studied in ChRCC, notably the recently introduced chromophobe tumor grade (CTG), which discounts the constitutive nuclear atypia in ChRCC. Studies have shown that CTG provides a superior prognostic value than FNG, and CTG is suggested by some authors as the preferred grading scheme for ChRCC. However, limited data suggest that CTG and stage are perhaps intercorrelated, and although CTG is associated with the outcome of ChRCC, its prognostic value may be diminished when pathologic stage is assessed. So far, validation studies regarding CTG were hampered by having few adverse events in the analyses because of the generally favorable outcome and the uncommon incidence of ChRCC. An evolving question is whether grading can be useful in needle core biopsy specimens with ChRCC, as conservative management such as active surveillance is being introduced and where clinical staging of extrarenal tumor extension (≥pT3) by imaging may not be accurate. Future definitive studies require larger multi-institutional accrual of ChRCCs to provide a better understanding of the prognostic value of grading ChRCC.